085 Systolic vs diastolic acquisition in cardiovascular magnetic resonance myocardial perfusion imaging. (16th May 2012) - Motwani, M; Fairbairn, T A; Larghat, A; Mather, A N; Biglands, J D; Radjenovic, A; Greenwood, J P; Plein, S
Abstract : Introduction: Although differences in systolic and diastolic myocardial blood flow (MBF) estimates have been shown in healthy volunteers, the impact of cardiac phase on detecting coronary artery disease (CAD) using cardiovascular magnetic resonance (CMR) myocardial perfusion imaging is unknown. The aim of this study was to compare MBF estimates in systole and diastole in patients with suspected CAD and determine if either phase has greater diagnostic accuracy. Methods: Following invasive coronary angiography, 40 patients (68% men, 64±8 yrs) underwent stress/rest perfusion-CMR (1.5T Philips) which was acquired at mid-systole and end-diastole simultaneously. Based on angiographic stenosis >70% (quantitative coronary angiography), patients were grouped as having "CAD" or "no CAD." In patients with CAD, myocardial segments were classified as "stenosis-dependent" (downstream of a significant stenosis) or "remote." For each segment, MBF (Fermi-constrained deconvolution) and myocardial perfusion reserve (MPR) were calculated. The diagnostic accuracy of each phase was determined with receiver operator characteristic analysis. Results: 21 patients (53%) had CAD. A typical example of a patient with ischaemia is shown in Abstract 085 figure 1 . Resting MBF was similar in the two cardiac phases for both normal and CAD patients (all p values >0.05). MBF at stress was greater in diastole than systole in normal, remote and stenosis-dependent segments (3.75±1.5 vs 3.15±1.1 ml/g/min; 2.75±1.20 vs 2.38±0.99 ml/g/min; 2.49±1.07 vs 2.23±0.90 ml/g/min; all p values <0.01). MPR was also greater in diastole than systole in all three segment groups (all p values <0.05) (Abstract 085 figure 2 ). On receiver operator characteristic analysis, the optimal MPR cut-off for the detection of CAD was 1.95 for systole and 2.04 for diastole (area under curve 0.82 vs 0.79; p=0.30). Conclusion: Estimates of stress MBF and MPR by perfusion-CMR in this study were greater in diastole than systole in normal and CAD patients. Although the diagnostic accuracy of both phases was similar, the MPR cut-off values were different. These observations are relevant to any form of dynamic myocardial perfusion assessment and are of particular importance to promising developments in 3D perfusion-CMR and CT perfusion imaging where the acquisition phase may be specifically chosen. Different estimates of MBF and different MPR cut-off values between phases mean a universal standard needs to be agreed for 3D acquisitions.